Depicting the Other Faith: A Bibliography Survey of Indonesian Muslim Polemics on Christianity - Ismatu Ropi (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
The demise of the Cultural Policy (cultuurstelsel) in the mid-nineteenth century inevitably changed the narrative history of the Indonesian archipelago. It was abvious that the policy generated immense profits for the Dutch colonial administration, allowing it to make a profit in addition to balancing its budget. Much of the surplus was sent to Netherlands itself and was used for public expenditures, thereby subsidizing the Dutch taxpayer. However, for the indiginous population of the East Indies, expecting those who were close to colonila agents, cultuurstelsel soon came to mean exploitation and impoverishment.DOI: 10.15408/sdi.v6i1.747